Art and Industrial Society: The Role of the Toronto Mechanic's Institute in the Promotion of Art, 1831-1883 - Ramsay, Ellen (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1999)
The Toronto Mechanics' Institute (1831-1883) served as one of the principle institutions of art instruction, the employment of artists (female and male), and exhibition of art in 19th century Toronto. Artists and illustrators now well known in the annals of Canadian art including Laura Bell, Mary Cooper, Richard Baigent, William Bengough, Robert Gagen, William Hind, Henry Martin, George Reid, Kivas Tulley, John Tully, and Å. Ê. Westmacott were amongst the list of teachers and exhibitors at this Institute which attracted 6,000 to 9,000 people and as many as 700 paintings and photographs to its Annual Exhibition by mid-century. Founded for the advancement of worker self-education in the period prior to the Rebellion, the Toronto Mechanics' Institute continued to play a vital role for theToronto working class in both practical design and fine art throughout the century until the emergence of public adult educational provisions in the latter quarter of the century. The minute books and annual reports of the Mechanics' Institute provide an instructive source for the researcher and demonstrate that contrary to some received wisdom that the mechanics' institutes were middle-class institutions, the Toronto Mechanics' Institute witnessed many lively debates on relevant social topics and remained committed to a working-class orientation throughout its existence despite the changing compositions of its Board. This article sets forth some archival findings and makes some theoretical refinements to the debates on the Mechanics' Institute in the hope of contributing to the on-going research.